The Effectiveness of Bawaslu’s Supervision in Maintaining the Neutrality of the State Civil Apparatus during Elections in Garut Regency - Yusuf Firdaus; Sarip; Urip Giyono (PT. Caesarindo Triloka Persada, 2026)
The neutrality of the State Civil Apparatus (ASN) constitutes an essential principle in ensuring democratic, honest, and fair elections in Indonesia. Nevertheless, violations of ASN neutrality continue to occur during electoral processes, including involvement in practical political activities, misuse of state facilities, and political support expressed through social media platforms. This study aims to analyze the legal effectiveness of the General Election Supervisory Agency’s (Bawaslu) supervision in maintaining ASN neutrality during elections in Garut Regency and to identify the factors influencing the implementation of such supervision. This research employed an empirical juridical qualitative approach. Data were collected through interviews, documentation studies, and literature reviews involving Bawaslu officials, ASN members, and relevant legal documents concerning election supervision and ASN neutrality. The findings indicate that Bawaslu has carried out preventive supervision through socialization programs, direct monitoring, institutional coordination, and handling of alleged neutrality violations. However, the effectiveness of supervision has not yet been fully optimal due to several obstacles, including limited supervisory authority, inadequate human resources, broad supervisory areas, low legal awareness among ASN, and persistent sociopolitical pressures within local bureaucratic structures. The study concludes that the effectiveness of Bawaslu’s supervision is influenced not only by the legal framework but also by institutional capacity, legal culture, and societal compliance with neutrality principles. Strengthening institutional coordination, supervisory authority, and legal awareness is therefore necessary to support democratic elections characterized by fairness, integrity, and bureaucratic professionalism.